2019
DOI: 10.1002/cnr2.1207
|View full text |Cite
|
Sign up to set email alerts
|

The RS4;11 cell line as a model for leukaemia with t(4;11)(q21;q23): Revised characterisation of cytogenetic features

Abstract: Background: Haematological malignancies harbouring rearrangements of the KMT2A gene represent a unique subtype of leukaemia, with biphenotypic clinical manifestations, a rapid and aggressive onset, and a generally poor prognosis. Chromosomal translocations involving KMT2A often cause the formation of oncogenic fusion genes, such as the most common translocation t(4;11)(q21;q23) producing the KMT2A-AFF1 chimera.Aim: The aim of this study was to confirm and review the cytogenetic and molecular features of the KM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…It has been shown that t(8;14) is less frequent in cases with wild-type CDKN2 [ 473 ]. Furthermore, RS4;11 (KMT2A-AFF1), a B-cell leukemic cell line containing isochromosome i(8q), shows a duplicated MYC gene [ 474 ]. The KMT2A-AFF1 rearrangement mostly participates in the leukemic progression as a second hit, and B-ALL patients with this fusion protein possess a significantly promoted MYC gene expression in comparison to patients with AML [ 475 , 476 ].…”
Section: The Role Of Myc In Hematopoiesis and Hematological Malignanciesmentioning
confidence: 99%
“…It has been shown that t(8;14) is less frequent in cases with wild-type CDKN2 [ 473 ]. Furthermore, RS4;11 (KMT2A-AFF1), a B-cell leukemic cell line containing isochromosome i(8q), shows a duplicated MYC gene [ 474 ]. The KMT2A-AFF1 rearrangement mostly participates in the leukemic progression as a second hit, and B-ALL patients with this fusion protein possess a significantly promoted MYC gene expression in comparison to patients with AML [ 475 , 476 ].…”
Section: The Role Of Myc In Hematopoiesis and Hematological Malignanciesmentioning
confidence: 99%
“…reported on a patient with therapy-related ALL who received a topoisomerase II inhibitor for induction chemotherapy. A higher frequency of MLL gene rearrangements, especially t(4;11), was observed in cases of therapy-related ALL compared to therapy-related AML.A recent novel study concludes that the RS4;11 cell line serves as an appropriate in vitro model for studying leukemia with t(4;11), potentially aiding in advancing research and achieving breakthroughs in understanding the relationship between CLN and chromosomal aberrations such as t(4;11) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human lymphoblastic leukemia cell line RS4;11 was obtained from the IRCCS SYNLAB SDN Biobank 31 . Cells were detained in IMDM medium, supplemented with 10% FBS, 10 mM Glutamine and the addition of 1 × Penicillin–Streptomycin solution (Lonza) and kept in a humidified incubator at 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%